Endovascular Management of Intracranial Atherosclerosis-Related Large Vessel Occlusion With the A Direct Aspiration First-Pass Thrombectomy Compared With Solumbra Technique - Li, Zhao-Shuo; Zhou, Teng-Fei; Li, Qiang; Guan, Min; Liu, Huan; Zhu, Liang-Fu; Wang, Zi-Liang; Li, Tian-Xiao; Gao, Bu-Lang (Frontiers in Neurology, 2021)
Background: To investigate the effect of the A Direct Aspiration First-Pass Thrombectomy (ADAPT) vs. Solumbra technique in the treatment of acute intracranial atherosclerosis-related large vessel occlusion (LVO). Methods: Patients with acute atherosclerosis-related LVO who had undergone endovascular treatment were retrospectively enrolled into two groups: The Solumbra and ADAPT groups. The clinical data were analyzed. Results: Patients (104) were enrolled with 48 in the Solumbra and 56 in the ADAPT group. The mean time from femoral access to recanalization was significantly (P < 0.05) shorter in the ADAPT than in the Solumbra group. The recanalization time at the first line was significantly shorter in the ADAPT group than in the Solumbra group (17 ± 10.21 vs. 26 ± 15.55 min, P = 0.02). However, the rate of switching to the alternative was significantly higher in the ADAPT group than that in the Solumbra group (46.42 vs. 33.33%, P = 0.01). Eighty-two patients had eventual recanalization, resulting in a final recanalization rate of 78.85%. At 3-month clinical follow-up for all patients, the good prognosis rate reached 51.92% with good prognosis in 24 patients (50%) in the Solumbra and 30 (53.57%) in the ADAPT group. The rate of symptomatic intracranial hemorrhage was 18.75% (n = 9) in the Solumbra and 19.64% (n = 11) in the ADAPT group. The mortality rate was 21.15% (22/104). Among 80 (76.92%) patients who had angiographic follow-up (3–30 months), five (6.25%) patients experienced in-stent stenosis, and two (2.5%) experienced asymptomatic stent occlusion. Conclusion: In patients with acute intracranial atherosclerosis-related LVO, clinical outcomes treated using the ADAPT technique are comparable with those using the Solumbra technique, and more patients need additional remedial measures if treated with the ADAPT technique.